2012
DOI: 10.1590/s0066-782x2012000400001
|View full text |Cite
|
Sign up to set email alerts
|

Utilização de terapêuticas comprovadamente úteis no tratamento da coronariopatia aguda: comparação entre diferentes regiões brasileiras. Análise do Registro Brasileiro de Síndromes Coronarianas Agudas (BRACE - Brazilian Registry on Acute Coronary Syndromes)

Abstract: Background: Little is known in our country about regional differences in the treatment of acute coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 5 publications
1
22
0
7
Order By: Relevance
“…They have also reported lower prescription rates of beta-blockers and thienopyridines. When compared to two other Brazilian registries 2,3 recently published, the drug prescription rates were higher in this registry, which can be explained by the method of selecting the centers and the profile of patients 3 .…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…They have also reported lower prescription rates of beta-blockers and thienopyridines. When compared to two other Brazilian registries 2,3 recently published, the drug prescription rates were higher in this registry, which can be explained by the method of selecting the centers and the profile of patients 3 .…”
Section: Discussionmentioning
confidence: 63%
“…Usually, ASA is highly used in all Brazilian 2,3 and international 14,16 registries. In this study sample, a high initial prescription rate of p2y12 inhibitors was observed, and, as compared to those registries previously published, that occurred to the detriment of the use of glycoprotein (GP) IIb/IIIa inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These records have become major documents that show the demography of the disorders involved 2, 3, 8 . The initial results of these records demonstrate the diversity of treatments conducted at a national level, including the regional inequality in the employment of reperfusion therapies 2 .…”
mentioning
confidence: 99%
“…These records have become major documents that show the demography of the disorders involved 2, 3, 8 . The initial results of these records demonstrate the diversity of treatments conducted at a national level, including the regional inequality in the employment of reperfusion therapies 2 . The use of these therapies relates, on the other hand, to lower mortality and lower rates of complications in the immediate follow-up of patients 3,8 .…”
mentioning
confidence: 99%